Overcoming the odds: high risk children from birth to adulthood - Werner, Emmy; Smith, Ruth (New York: Cornell University, 1995)
Contents : The context of the study,ordinary people,the reilient children in adulthood,teenage mothers in later years,delinquents with and without records of adult crimes,mental health problems : trouble youths grown up,stressful events in childhood and youth and adult adaptation,protective factors and adult adaptation,summing up
Keywords: Children - Longitudinal studies